Human Skin Safety Test of Green Tea Cell Extracts in Condition of Allergic Contact Dermatitis - Kim, Hyun Kyu (The Korean Society of Toxicology, 2012)
Various kinds of positive effects of green tea extracts had been studied for long time which included anti-inflammation, anti-aging, and cardiometabolic effects. Although topical steroid and non-steroidal calcineurin inhibitors may control clinical symptoms of allergic contact dermatitis, some of patients also present allergic reaction to these topical agents. Therefore, we have tried green tea extracts for managing this skin disorder with expectation of anti-inflammatory effect without potential side effects including skin irritation and toxic responses. The toxicity test of green tea extract also did not show any sign of irritation in the skin throughout the test period. Moderate severity of allergic contact dermatitis presented satisfactory clinical outcome at second week follow-up which was final visit of outpatient. This result mean that green tea extract has a positive effect for managing allergic contact dermatitis but its potency and efficacy seem to be so not strong enough to control moderate severity allergy skin lesion. In this pilot study, we were able to conclude that green tea cell extracts might be applied for potential anti-inflammatory soaking without skin toxicity.